Biodiversity prospecting : using genetic resources for sustainable development - Reid, Walter V.; World Resources Institute; Instituto Nacional de Biodiversidad (Costa Rica); Rainforest Alliance; African Centre for Technology Studies ([Washington, D.C.] : World Resources Institute (WRI), USA ; [Santo Domingo, Heredia] : Instituto Nacional de Biodiversidad (INBio), Costa Rica ; [New York, N.Y.] : Rainforest Alliance, USA ; [Nairobi] : African Centre for Technology Studies (ACTS), Kenya, 1993)
"A Contribution to the WRI/IUCN/UNEP Global biodiversity strategy."
"A Contribution to the WRI/IUCN/UNEP Global biodiversity strategy."
"A World Resources Institute book"--P. [1] of cover.
Includes bibliographical references and index.
oif 05/08/16
Loan
Keywords: Biodiversity conservation; Sustainable development; Germplasm resources